Bioinspired Poly(vinyl alcohol) Film Actuator Powered by Water Evaporation under Ambient Conditions. Issue 6 (30th April 2020) - Wang, Sitong; Yan, Shuang; Zhang, Li; Zhao, Huhu; Yang, Tian; Li, Feibo; Li, Huanjun
Abstract: Soft humidity‐responsive materials are highly desirable for applications such as actuators, sensors, generators, and soft robots. However, it remains a huge challenge to develop a durable, cost‐effective, fast responsive version of such a smart material powered by water evaporation at ambient conditions. Herein, this challenge is addressed to demonstrate sustained response to humidity gradient from ambient water evaporation by using common poly(vinyl alcohol) (PVA) film as an actuator. The resultant PVA film displays strong mechanical properties in both dry and wet conditions, which cause rapid adsorption and desorption of water vapor to drive the film undergoing swift locomotion with flipping frequency of up to 65 r min ‐1 . Based on these features, a mimosa inspired humidity‐responsive actuator is developed which is far superior in response speed and durability than real mimosa. Furthermore, it is demonstrated that the film actuator can convert water evaporation energy into electricity when attached to a piezoelectric element. Abstract : A bioinspired actuator made of common poly(vinyl alcohol) film demonstrates sustained response to humidity gradient from ambient water evaporation and successfully convert evaporation energy into electricity when attached to a piezoelectric element.